The Prince : The Secret Story of the World's Most Intriguing Royal, Prince Bandar bin Sultan - Simpson, William, 1948- (New York Regan An Imprint of Harper Collins Publisher Books, 2006)
A riveting portrait of one of the most enigmatic yet influential power brokers in America - Prince Bandar bin Sultan bin Abdul Aziz Al-Saud, the Saudi Arabian Ambassador to the United States from 1983 to 2005. For the last two and a half decades, the United States and Saudi Arabia have had a very special relationship - through war, oil crises, and global terrorism. At a time when understanding our friends is as important as knowing our enemies, understanding Prince Bandar bin Sultan may be the key to figuring out the Saudis.
Include Picture, Notes and Index
Keywords: Bin Sultan, Bandar, Prince -- Diplomatic Relations -- Ambassadors -- Saudi Arabia -- Biography -- Princes -- Saudi Arabia -- Biography